Not-for-profit observational study to evaluate the quality and safety of care in outliers hospitalized with medical diseases - Study Protocol of Safety Issues and SurvIval For Medical Outliers (SISIFO study) - Micaela La Regina; Chiara Vertulli; Gualberto Gussoni; Andrea Fontanella; Giorgio Ballardini; Antonio Brucato; Francesco Orlandini; Giovanni Murialdo; Mauro Campanini; Dario Manfellotto (Italian Journal of Medicine, 2021)
The progressive cutting of hospital beds in some health systems, together with the increased needs related to the aging population, has led to the phenomenon of patients hospitalized outside the appropriate ward (outliers). This is particularly relevant in the context of Internal Medicine. Despite its relevance in daily clinical practice, available evidence for the potential impact of this phenomenon is limited. The aim of this study is to evaluate the effects of this situation on patients’ outcomes and possibly identify organizational and managerial aspects related to the presence of outliers. The multicenter, observational, prospective Study Protocol of Safety Issues and SurvIval For Medical Outliers (SISIFO) was promoted by the Italian Federation of Associations of Hospital Doctors on Internal Medicine (FADOI). The primary study endpoint is the evaluation of in-hospital mortality in outliers versus controls. A sample size of 2400 patients has been estimated by assuming a mortality rate of 12% and 8% in outliers and controls, respectively. By virtue of the multicentric dimension, the expected number of patients, and the controlled design, the FADOI-SISIFO study might provide interesting and useful findings to better manage the phenomenon of outliers.